How does discharge status impact suicide risk in military veterans?. Issue 1 (2nd January 2019) - Barr, Nicholas; Kintzle, Sara; Alday, Eva; Castro, Carl
ABSTRACT: Little is known about over 125, 000 veterans who received non-honorable military discharges since 2001, even though these veterans face substantial barriers to obtaining services and are likely to be at high risk for negative mental and behavioral health outcomes including suicide. Seven-hundred twenty-two veterans living the in the San Francisco Bay Area participated in the study. The sample comprised honorably discharged ( n  = 508) and non-honorably discharged veterans ( n  = 214). T- tests were used to compare means on predictors of suicide risk including Posttraumatic Stress Disorder (PTSD), depression, alcohol use, somatic symptoms, and physical disability. A series of regression models tested relationships between predictors, discharge status, and suicide risk. Non-honorably discharged veterans demonstrated higher mean scores than honorably discharged veterans on all predictors. In regression models, somatic symptoms (β = 0.22, p  < 0.001), physical disability (β = 0.16, p  < 0.05), and discharge status (β = 0.33, p  < 0.001) were associated with suicide risk. The final model showed an interaction effect for discharge status on the relationship between somatic symptoms and suicide risk (β = 0.16, p  < 0.05). Non-honorably discharged veterans showed higher rates of mental and physical health problems and suicide risk compared to honorably discharged veterans. The magnitude of the relationship between somatic symptoms and suicide risk was significantly greater in non-honorably discharged veterans.